Correlation between knowledge of HIV, attitudes and perceptions of HIV and a willingness to test for HIV at a regional hospital in KwaZulu-Natal, South Africa - Emeka E. Orisakwe; Andrew J. Ross; Peter O. Ocholla (AOSIS, 2012)
Background: With millions of South Africans infected with human immunodeficiency virus (HIV) and less than 10% of the population aware of their HIV status, HIV counselling and testing (HCT) is the first step in any attempt to reduce the number of new infections. For those who test negative, HCT personalises the risks and reinforces preventative messages whilst for those who are positive, it is the gateway to accessing counselling and care. The Health Belief Model postulates that knowledge and attitude influence behaviour. The aim of this study was to determine whether knowledge of HIV and the attitude of patients referred for HCT correlated with a willingness to test for HIV. Methods: One hundred and seventy two patients referred for HCT were randomly selected over a three month period. Data were collected by a research assistant using the modified standardised World Health Organization (WHO)-Global AIDS Project (GAP) questionnaire. Results: Ninety per cent of the participants demonstrated sound knowledge of HIV, acquired immune deficiency syndrome (AIDS) and HCT. Despite the 90% of the participants with sound knowledge only 71.5% of the participants tested for HIV. There was no statistically significant difference in knowledge between those who tested and those who did not test for HIV. Twenty five per cent of those who refused to test stated that they had already made up their mind not to test for HIV before the counselling session. Conclusions: Despite excellent knowledge of HIV, a significant number of patients referred for HCT do not test for HIV.